From shame to game in one hundred years: an economic model of the rise in premarital sex and its de-stigmatization - Jesús Fernández-Villaverde; Jeremy Greenwood; Nezih Guner (Institute for the Study of Labor (IZA), 2010)
Societies socialize children about many things, including sex. Socialization is costly. It uses scarce resources, such as time and effort. Parents weigh the marginal gains from socialization against its costs. Those at the lower end of the socioeconomic scale indoctrinate their daughters less than others about the perils of premarital sex, because the latter will lose less from an out-of-wedlock birth. Modern contraceptives have profoundly affected the calculus for instilling sexual mores, leading to a de-stigmatization of sex. As contraception has become more effective there is less need for parents, churches and states to inculcate sexual mores. Technology affects culture.
Keywords: D1; J11; J12; J13; E1; 330; Children; church and state; contraception; culture; parents; premarital sex; out-of-wedlock births; socialization; stigmatization; technological progress; Sexualität; Sozialisation; Kinder; Jugendliche; Soziale Werte; Sozialer Wandel; Nichteheliche Kinder; Theorie; Großbritannien; USA